PENERAPAN THE DUE CARE THEORY DALAM PRAKTIK UPSELLING (STUDI KASUS J.CO SUMMARECON BEKASI DAN KONSUMEN TANIA): Application of The Due Care theory in Upselling Practices (Case Study of J.CO Summarecon Bekasi and Consumer Tania) - Risma Berlian Abadi; Halim, Suci Lestari (Reformasi Hukum Trisakti, 2026)
Upselling practices in the food and beverage sector are increasingly used by businesses to boost sales. However, in the case of J.CO Summarecon Mall Bekasi involving the consumer Tania, an imbalance of information regarding product bundling offers was found, potentially disadvantaging the consumer. The problem formulation in this article is how the application of the due care theory relates to the upselling practice. This research uses a normative research type with a descriptive approach, employing secondary data supported by interviews, data were collected through a library research, which are analyzed qualitatively and concluded using a deductive method. The analysis evaluated that the application of the Due Care Theory in the upselling practices carried out by J.CO Summarecon Mall Bekasi toward consumer Tania indicates a lack of clarity in price information that has the potential to disadvantage consumers and is inconsistent with Article 4(c) jo. Article 7(b) jo. Article 10(a) of Law Number 8 of 1999 on Consumer Protection.